Model systemu rekompensat dla inwestorów giełdowych w Polsce na tle tendencji integracyjnych rynku finansowego w Unii Europejskiej - Janik, Bogna (Model of Polish investor compensation scheme versus integration - tendencies of EU financial market, 2006)
Creating unified market within UE is connected with so called Lisbon Strategy whose objective is making the union the most competitive economy in the world. One of the models to achieve this target is harmonizing regulations of financial services market and aiming at creating indispensable security base for customer of investment institutions, as well as common requirements for all the investment institutions in member countries (e.g. Investor Compensation Directive (ICD) 1997/9/EC, Second Investment services Directive on Market Structure (ISD2) 2004/39/EC). In spite of controversies concerning various conceptions of market operation, in majority of developed market economies there are regulations protecting so called small customers against the loss of the means assigned to investment institutions. All those regulations, as well as the character of the Polish financial services market, create problems concerning the shape of the Polish system for protection of customers on the changing financial market. Investor compensation scheme is a part of stock market protection system protecting small investor against the loss of financial instruments and means during bankrupcy of investment institutions. This scheme does not protect the inwestor against the results of his wrong financial decisions, however it provides protection against the loss of assets resulting from lack of insolvency. The model of Polish scheme is manifested in 4 variants. Each of them takes into account mesurable factors influencing the scheme. The variants are applicable either instantly, or in future depending on the development integreted European financial market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 139-155